Antibody‐Secreting Cell Specificity in Labial Salivary Glands Reflects the Clinical Presentation and Serology in Patients With Sjögren's Syndrome1. Issue 12 (December 2014) - Maier‐Moore, Jacen S.; Koelsch, Kristi A.; Smith, Kenneth; Lessard, Christopher J.; Radfar, Lida; Lewis, David; Kurien, Biji T.; Wolska, Nina; Deshmukh, Umesh; Rasmussen, Astrid; Sivils, Kathy L.; James, Judith A.; et al.
<x xml:space="preserve">Abstract</x> Objective The serologic hallmark of primary Sjögren's syndrome (SS) is the presence of IgG antibodies specific for Ro (SSA) and La (SSB). The molecular characteristics of gland‐derived B cells at the site of primary SS inflammation have been described previously; however, parallels between glandular antibody‐secreting cells (ASCs) and serologic antibody specificities have not been evaluated. We used recombinant monoclonal antibody (mAb) technology to study the specificities of salivary gland (SG)–derived ASCs, evaluate their molecular characteristics, and identify IgG antibody specificity. Methods Human antibodies were generated from glandular IgG ASCs. Heavy chain and light chain use and immunoglobulin subclass were analyzed by sequencing. Enzyme‐linked immunosorbent assay, indirect immunofluorescence, enzyme immunoassay, and 35S‐labeled protein immunoprecipitation analysis were used to determine antibody specificity. Results Evaluation of single ASCs in SG biopsy specimens from a patient with primary SS and a patient with SS and overlapping systemic lupus erythematosus revealed significant concordance between serum autoantibody and glandular ASC specificities. Gland‐derived ASC heavy chains and light chains were extensively somatically hypermutated, which is indicative of antigen‐driven responses. Specifically, we produced the first fully human mAb derived from SGs. Conclusion In patients with SS, the SGs are a site for the production of antibodies that extend beyond the canonical Ro and/or La SS specificities. Glandular antibody production strongly reflected the serologic humoral response in the 2 patients whom we studied.